2017
DOI: 10.1111/jocs.13250
|View full text |Cite
|
Sign up to set email alerts
|

The use of preoperative aspirin in cardiac surgery: A systematic review and meta-analysis

Abstract: Preoperative aspirin increases the risk for postoperative bleeding. However, this did not result in an increased need for chest re-exploration and did not increase the rates of PRBC transfusion when preoperative low-dose (≤160 mg/d) aspirin was administered. Aspirin at any dose is associated with decreased mortality and AKI and low-dose aspirin (≤160 mg/d) decreases the incidence of perioperative MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 61 publications
2
21
1
1
Order By: Relevance
“…In a study, Lawrence et al 5 performed revision surgery due to bleeding in 3.6% of the patients, consistent with our findings. Although revision surgery due to bleeding in the postoperative period has been associated with increased mortality 6 , we observed no mortality in patients who underwent revision surgery.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a study, Lawrence et al 5 performed revision surgery due to bleeding in 3.6% of the patients, consistent with our findings. Although revision surgery due to bleeding in the postoperative period has been associated with increased mortality 6 , we observed no mortality in patients who underwent revision surgery.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, a transient loss of platelet function can be seen after CABG under CPB 7 . However, preoperative antiaggregant use, particularly acetylsalicylic acid has not been associated with postoperative bleeding requiring revision surgery with a mortality-reducing effect 6 . Therefore, in our study, all patients were given premedication on the night before surgery and were operated under acetylsalicylic acid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Further, the 2017 meta-analysis found a slightly higher rate of RBC transfusion in patients with continued aspirin administration but no difference in chest drainage output or incidence of repeat thoracotomy. 21 In contrast, the ATACAS trial found no change in bleeding risk due to continued aspirin intake. 23 The latter might, at least partially, be explained by the use of antifibrinolytics in the ATACAS study.…”
Section: Aspirinmentioning
confidence: 98%
“…Modified after Bolliger et al 20 and Mahla et al 12 studies including nearly 30,000 patients undergoing cardiac surgery (>89% CABG surgery), the use of preoperative aspirin was associated with reductions in early mortality, acute kidney injury, and myocardial infarction. 21 The positive effects of preoperative aspirin were mainly driven by observational studies. A more recent retrospective propensity score analysis suggested that discontinuing aspirin before CABG surgery might increase mortality and major thromboembolic events by more than 50%.…”
Section: Aspirinmentioning
confidence: 99%
“…4 The use of an antiplatelet agent, such as aspirin, either before and immediately after surgery, was an attempt to reduce the consequences of a problem that could lead to occlusion of grafts, mainly venous. It was demonstrated that aspirin reduces early mortality and incidence of acute myocardial infarction 5 and improves patency rate after CABG. 6 Aspirin, however, has some drawbacks.…”
mentioning
confidence: 99%